2012
DOI: 10.1007/s00586-012-2372-2
|View full text |Cite
|
Sign up to set email alerts
|

Apical vertebral derotation in the posterior treatment of adolescent idiopathic scoliosis: myth or reality?

Abstract: Introduction Direct apical vertebral rotation represents an important goal of posterior surgery for thoracic adolescent idiopathic scoliosis (AIS), so as to obtain a better cosmetic effect and to avoid posterior thoracoplasty. However, the real effectiveness in correction of vertebral rotation, using posterior only procedures, is still open to debate. The aim of the present study is to compare the correction of axial apical rotation obtained with direct rotation procedure versus simple concave rod rotation, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 38 publications
2
38
1
1
Order By: Relevance
“…Surprisingly, the torsion index reduction reached 44 %, and the apical vertebral rotation correction averaged 48.3 %, approaching the rates reported in the literature obtained using direct vertebral rotation (DVR) (42.5-64 %) [35][36][37] while obviating potential risks associated with DVR [38]. The unexpectedly high apical vertebral rotational reduction observed in the present patients might be explained by the fact that the corrective maneuver was mediated simultaneously by both rods, preassembled using fixed transverse connectors (Fig.…”
Section: Low Dose Biplanar Stereoradiographysupporting
confidence: 52%
“…Surprisingly, the torsion index reduction reached 44 %, and the apical vertebral rotation correction averaged 48.3 %, approaching the rates reported in the literature obtained using direct vertebral rotation (DVR) (42.5-64 %) [35][36][37] while obviating potential risks associated with DVR [38]. The unexpectedly high apical vertebral rotational reduction observed in the present patients might be explained by the fact that the corrective maneuver was mediated simultaneously by both rods, preassembled using fixed transverse connectors (Fig.…”
Section: Low Dose Biplanar Stereoradiographysupporting
confidence: 52%
“…Reported efficacy of vertebral derotation varies widely, yet direct vertebral rotation showed the significantly better reduction of apical rotation over other methods [5,8,[30][31][32]. In our series, axial rotation changed significantly by 31.8% in DVR group comparing to 8.6% in non-DVR.…”
Section: Discussionmentioning
confidence: 48%
“…Several authors reported similar results. Di Silvestre et al, Kadoury et al, Samandi et al presented 8-10% better correction in coronal plane caused by DVR application [5][6][7]. In Lee's and Suk's papers, the differences were even more significant in favor of DVR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations